2021
DOI: 10.3390/cancers13225688
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Membrane Antigen in Anaplastic and Poorly Differentiated Thyroid Cancer—A New Diagnostic and Therapeutic Target?

Abstract: Several studies have demonstrated an expression of the prostate-specific membrane antigen (PSMA) in the cancer-related neovasculature of thyroid malignancies. Due to the poor prognosis and limited therapeutic options for patients with anaplastic (ATC) and poorly differentiated (PDTC) thyroid carcinoma, the aim of our study was to investigate the theranostic approach of PSMA expression in these patients. The PSMA uptake on Gallium-68 (68Ga)-PSMA-positron emission tomography/computed tomography (PET/CT) and gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Moreover, from the comparative analyses, it emerged that the PSMA expression was higher in the primary tumors than metastatic sites due to their different microenvironments and signalling pathways. Furthermore, 7 out of 8 patients who underwent both 18 F-FDG PET/CT and 68 GaPSMA PET/CT showed higher FDG uptake rates compared to PSMA uptake, showing that 18 F-FDG-PET/CT still has higher accuracy than 68 Ga-PSMA PET/CT in detecting more aggressive thyroid cancer histotypes [ 20 ]. On the other hand, de Vries et al retrospectively analyzed a small cohort of 5 patients affected by radioiodine-refractory thyroid cancer by using the dual-tracer approach ( 18 F-FDG and 68 Ga-PSMA PET/CT).…”
Section: Thyroid Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, from the comparative analyses, it emerged that the PSMA expression was higher in the primary tumors than metastatic sites due to their different microenvironments and signalling pathways. Furthermore, 7 out of 8 patients who underwent both 18 F-FDG PET/CT and 68 GaPSMA PET/CT showed higher FDG uptake rates compared to PSMA uptake, showing that 18 F-FDG-PET/CT still has higher accuracy than 68 Ga-PSMA PET/CT in detecting more aggressive thyroid cancer histotypes [ 20 ]. On the other hand, de Vries et al retrospectively analyzed a small cohort of 5 patients affected by radioiodine-refractory thyroid cancer by using the dual-tracer approach ( 18 F-FDG and 68 Ga-PSMA PET/CT).…”
Section: Thyroid Cancermentioning
confidence: 99%
“…In particular, the 68 Ga-PSMA PET/CT performed 5 weeks after the second cycle showed size decreases in several lung lesions, response of the liver metastases and stable disease of the cervical metastases [ 21 ]. Finally, Wächter et al reported one PDTC patient who received two cycles of 177 Lu-PSMA therapy, based on high PSMA uptake based on PSMA PET/CT and 18 F-FDG-negative scans, with a time interval of 8 weeks (cumulative dose 13.7 GBq), showing stable disease for 7 months, followed by an increase in Tg levels and the appearance of 18 F-FDG-positive metastases [ 20 ].…”
Section: Thyroid Cancermentioning
confidence: 99%
“…Theranostics are of particular interest for such aggressive cancers, but are challenging to evaluate in such rare malignancies; clinically available radiotracers have been used in few patients on an experimental basis. Ga68-PSMA PET/CT and MRI were recently performed among a small cohorts of patients with PDTC and ATC [95,96], with variable results: 74% of poorly differentiated tumor metastases were detected in one small study, while only 11% of PDTC metastases (and no ATC metastases) were detected in another. In the latter study, only one patient underwent treatment with Lu-177 PSMA, stabilizing their disease for 7 months [96].…”
Section: Poorly Differentiated (Pdtc) and Anaplastic Thyroid Cancer (...mentioning
confidence: 99%
“…Ga68-PSMA PET/CT and MRI were recently performed among a small cohorts of patients with PDTC and ATC [95,96], with variable results: 74% of poorly differentiated tumor metastases were detected in one small study, while only 11% of PDTC metastases (and no ATC metastases) were detected in another. In the latter study, only one patient underwent treatment with Lu-177 PSMA, stabilizing their disease for 7 months [96].…”
Section: Poorly Differentiated (Pdtc) and Anaplastic Thyroid Cancer (...mentioning
confidence: 99%
“…It should be noted that differentiated and undifferentiated thyroid cancer can be positive on PSMA-targeting PET-CT that is done for prostate cancer [ 85 ]. This may support a future theranostic target in patients with treatment-refractory DTC or anaplastic thyroid cancer [ 86 ]. Incidental focal uptake of either FDG or a PSMA-ligand in the thyroid or in cervical nodes in a patient with prior thyroid cancer should prompt additional evaluation.…”
Section: Head and Neck Cancermentioning
confidence: 99%